The Influence of Spiritual Leadership on Organizational Citizenship Behavior: Workplace Spirituality and Thriving at Work as Mediation - Ramadhani Gafar Utama; Rr. Sri Handari Wahyuningsih; Arni Surwanti (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
This study looks at the mediating role of workplace spirituality and thriving at work on the influence of spiritual leadership on organizational citizenship behavior. The research subject used was teachers in Madrasah Mu'allimin Muhammadiyah Yogyakarta. The sampling technique used was saturated sampling, with 102 returned questionnaire answers. The data obtained were analyzed using SEM with PLS software. The results include (1) Spiritual leadership affected workplace spirituality, (2) Spiritual leadership affected thriving at work, (3) Workplace spirituality affected thriving at work, (4) Spiritual leadership affected organizational citizenship behavior, (5) Workplace spirituality affected organizational citizenship behavior, (6) Thriving at work affected organizational citizenship behavior, (7) Workplace spirituality mediated the influence of spiritual leadership on organizational citizenship behavior (8) Thriving at work mediated the influence of spiritual leadership on organizational citizenship behavior. Based on the results, organizational citizenship behavior could be improved with spiritual leadership, workplace spirituality, and thriving at work. Workplace spirituality and thriving at work as mediating variables could be applied to spiritual leadership approach methods to improve organizational citizenship behavior.